Sustainable Risk Management at Bukit Selatan Coffee Shop Based on ISO 31000:2018 - C Nike Septivani; Antonia Laratmase; Muhammad Rehan Sayuti (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2026)
This study aims to analyze sustainable risk management at Bukit Selatan Coffee Shop in Tebet, South Jakarta, based on ISO 31000:2018. A qualitative case-study approach was employed. Data were collected through interviews with the owner and employees, observation of operational activities, and supporting documentation. The analysis followed the ISO 31000:2018 process: establishing context, risk identification, risk analysis (likelihood and impact), risk evaluation to set priorities, and the formulation of risk treatments. The findings reveal key risks across financial, operational, human resource, and market aspects. High-priority risks include service delays during peak hours, breakdowns of critical equipment, and fluctuations in raw material prices. Recommended treatments focus on risk reduction through standard operating procedures, improved shift scheduling, barista training, preventive maintenance, inventory control, and supplier diversification, supported by continuous monitoring and periodic review. Implementing the ISO 31000:2018 framework strengthens the shop’s preparedness for uncertainty, supports operational stability, and enhances business sustainability amid intense competition.